2017
DOI: 10.1155/2017/6431818
|View full text |Cite
|
Sign up to set email alerts
|

Quality Comparison of Hawthorn Wines Fermented by Saccharomyces cerevisiae with and without Pulp Contact and Pectase Treatment

Abstract: This study evaluated the chemical and volatile composition of hawthorn wines fermented with Saccharomyces cerevisiae A3.12 with and without pulp contact and pectase treatment during fermentation. The results indicated that the addition of pectase was in favor of pH decrease and clarification. The pectase-treated wines had significantly higher concentrations of acetic acid, ethyl octanoate, and isoamyl acetate than the non-enzyme-treated wines. Furthermore, the nonextracted wines had significantly higher concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…In dotted hawthorn, ethyl hexanoate constituted 26.5% of all volatile components, but in beer, ethyl hexanoate constituted only 3.9% of all volatiles. In a study about wines made from hawthorn fruit juice, conducted by Zhang et al [47], it was shown that concentration of ethyl hexanoate in wines was 7 times higher than in BJ, 10 times higher than in BC, and similar to the concentration in BF. Another ester identified in hawthorn fruit and all tested beers was ethyl (4E)-4-decenoate, which is characterised by fruit (pineapple), cognac and wax flavours [48,49].…”
Section: Concentration Of Volatile Compounds In Tested Beersmentioning
confidence: 93%
“…In dotted hawthorn, ethyl hexanoate constituted 26.5% of all volatile components, but in beer, ethyl hexanoate constituted only 3.9% of all volatiles. In a study about wines made from hawthorn fruit juice, conducted by Zhang et al [47], it was shown that concentration of ethyl hexanoate in wines was 7 times higher than in BJ, 10 times higher than in BC, and similar to the concentration in BF. Another ester identified in hawthorn fruit and all tested beers was ethyl (4E)-4-decenoate, which is characterised by fruit (pineapple), cognac and wax flavours [48,49].…”
Section: Concentration Of Volatile Compounds In Tested Beersmentioning
confidence: 93%
“…Beers produced from the North American shrub, star-spotted hawthorn, not only have a higher antioxidant capacity and higher polyphenol concentration, but also have a greater degree of improvement in taste, aroma, clarity, and overall impression [ 61 ]. Treatment of hawthorn wine with pectinase facilitated the reduction of pH and the release of methanol in the wine and accelerated the clarification of hawthorn wine [ 62 ].…”
Section: Applications In Food Productsmentioning
confidence: 99%
“…At present, there is little information and research on hawthorn’s anticancer effects. However, the bioactive substances contained in hawthorn are believed to have beneficial effects on human cancer cells [ 62 ]. The anticancer effects of hawthorn can be divided into two main areas: hawthorn extract and hawthorn isolated compounds.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Wykorzystanie pektynaz w czasie fermentacji może pozytywnie wpłynąć na klarowność wina oraz ułatwić jego filtrację, jednak wiąże się ze zwiększeniem zawartości szkodliwego dla organizmu alkoholu metylowego w gotowym produkcie. Fermentacja wraz z pulpą owocową ma pozytywny wpływ na aromat gotowego wina [43]. Zawartość cukrów w owocach głogu, średnio na poziomie 13 % [4] sprawia, że wino powstałe poprzez fermentację takiego moszczu posiadałoby niskie stężenie alkoholu etylowego.…”
Section: Problemy Technologiczne Podczas Przetwarzania Owoców Oraz Ic...unclassified